1994
DOI: 10.1007/bf00762742
|View full text |Cite
|
Sign up to set email alerts
|

Tight nucleotide binding sites and ATPase activities of theRhodospirillum rubrum RrF1-ATPase as compared to spinach chloroplast CF1-ATPase

Abstract: Solubilized Rhodospirillum rubrum RrF1-ATPase, depleted of loosely bound nucleotides, retains 2.6 mol of tightly bound ATP and ADP/mol of enzyme. Incubation of the depleted RrF1 with Mg(2+)-ATP or Mg(2+)-AMP-PNP, followed by passage through two successive Sephadex centrifuge columns, results in retention of a maximal number of 4 mol of tightly bound nucleotides/mol of RrF1. They include 1.5 mol of nonexchangeable ATP, whereas all tightly bound ADP is fully exchangeable. A similar retention of only four out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This mutant complex was expressed and purified in large amounts and responded to the ␥ C thiol modulation, but even its DTT-reduced MgATPase activity reached at the most 5 units/mg. Furthermore, no CaATPase activity has been reported in this mutant TF 1 -␣ 3 ␤ 3 ␥ complex, probably because in the native TF 1 , unlike in RrF 1 (Table I) and CF 1 (30), the CaATPase activity is 10-fold lower than its MgATPase activity (43).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This mutant complex was expressed and purified in large amounts and responded to the ␥ C thiol modulation, but even its DTT-reduced MgATPase activity reached at the most 5 units/mg. Furthermore, no CaATPase activity has been reported in this mutant TF 1 -␣ 3 ␤ 3 ␥ complex, probably because in the native TF 1 , unlike in RrF 1 (Table I) and CF 1 (30), the CaATPase activity is 10-fold lower than its MgATPase activity (43).…”
Section: Discussionmentioning
confidence: 77%
“…Since azide does not inhibit the CaATPase activity, another inhibitor will be required for such comparative studies. A very suitable candidate is the specific CF 1 effector tentoxin, which at low concentrations inhibits but at high concentrations stimulates both CF 1 Ca-and MgATPase activities (30). RrF 1 is, however, completely resistant to tentoxin.…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid enzyme assembly exhibited several properties distinct from those of the native RrF 1 and CF 1 enzymes and from the earlier tested hybrid assembly [19,33]. The hybrid most closely resembled the complex in that both enzymes hydrolyze MgATP very slowly in the absence of stimulating oxyanions while both have significant rates of Ca‐ATPase activity.…”
Section: Discussionmentioning
confidence: 84%
“…The activities of both the and enzymes continued to increase in parallel at tentoxin concentrations up to 400 µ m (not shown). As the native R. rubrum F 1 enzyme is neither inhibited nor stimulated by tentoxin [33], the result suggested that the CF 1 β subunit was responsible for conferring tentoxin stimulation upon the enzyme. This surprising result was confirmed by an experiment in which the wild‐type CF 1 β subunit was replaced with a mutant CF 1 β subunit in which the aspartate residue at position 83 had been replaced with leucine.…”
Section: Resultsmentioning
confidence: 99%
“…ATPase activity was assayed with 5 mM MgCI2 and 0.2 mM ATE and when added 2 mM azide, 16 mM octylglucoside and 10 mM sulfite. bData modified from Weiss et al (1994). ATPase activity was assayed with 2 mM MgCI2 and 4 mM ATE The concentrations of added effectors were as for RrFt-cq/.31, and when stated low tentoxin, 1/~M and high tentoxin, 100/zM.…”
Section: B 1 Soluble Atpase Activitiesmentioning
confidence: 99%